PENGARUH LATIHAN LADDER DRILLS TERHADAP KETERAMPILAN DRIBBLING SEPAK BOLA DI SMAN 5 PONTIANAK - Ammar, Muhammad; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is not yet known whether there is an effect of ladder drills training on dribbling skills of SMAN 5 Pontianak extracurricular participants? The purpose of this study was to determine the effect of ladder drills training on the dribbling skills of SMAN 5 Pontianak extracurricular participants. The method used is an experiment with the form of Pre Experimental Design in the form of pretest-posstest one group design. The population in this study were extracurricular students of SMAN 5 Pontianak, a total sample of 20 people.Based on the data obtained by the results of the calculation of the average value of pretest 15.01 and posttest 14.5. The calculation results obtained t-count = 7.178, then compared with dk = N-1 = 19 and a significance level of 5% obtained t table = 1.729. Because the count> t table or 7.178> 1,729, it can be said that Ho is rejected and Ha is accepted, with a percentage increase of 3.3%, there is the effect of ladder drills training on the dribbling skills of soccer extracurricular participants.Keywords: Ladder Drills, Dribbling, Sepak bolaAbstractThe problem in this study is not yet known whether there is an effect of ladder drills training on dribbling skills of SMAN 5 Pontianak extracurricular participants? The purpose of this study was to determine the effect of ladder drills training on the dribbling skills of SMAN 5 Pontianak extracurricular participants. The method used is an experiment with the form of Pre Experimental Design in the form of pretest-posstest one group design. The population in this study were extracurricular students of SMAN 5 Pontianak, a total sample of 20 people.Based on the data obtained by the results of the calculation of the average value of pretest 15.01 and posttest 14.5. The calculation results obtained t-count = 7.178, then compared with dk = N-1 = 19 and a significance level of 5% obtained t table = 1.729. Because the count> t table or 7.178> 1,729, it can be said that Ho is rejected and Ha is accepted, with a percentage increase of 3.3%, there is the effect of ladder drills training on the dribbling skills of soccer extracurricular participants. Keywords: Ladder Drills, Dribbling, Sepak bola